An observational study of 100 cases of 25μg oral misoprostol for induction of labour in term pregnancy - Gupta, Nidhi S.; Prajapati, Shetal S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Labour induction is a clinical intervention that has the potential to confer major benefits to the mother and new born when continuation of pregnancy poses a risk/danger to the outcome of pregnancy. Misoprostol is an ideal agent for induction of labour, particularly in settings where the use of prostaglandin E2 is not possible owing to lack of availability, facilities for storage, or financial constraints. It is stable at room temperature, relatively inexpensive and can be given via several routes (oral, vaginal, sublingual, and buccal). Methods: It is an observational study of 100 cases conducted in the labour room of a Tertiary Care Government Hospital, Rajkot over a span from January 2016 to March 2017. After patient selection as per inclusion criteria and written informed consent after evaluating patients were enrolled in the study. Tablet misoprostol 25 microgram given orally every 4 hourly with maximum of 5 doses till the patient was in active stage of labour. Results: Maximum patients delivered by a single dose of Tab. Misoprostol (35%), the mean induction delivery interval was 11.44 hours. Most of the women delivered by vaginal route (88%) without any maternal complications like PPH, cervical/vaginal tear and uterine rupture. Only 4 cases out of 100 of failed induction for which LSCS was taken. Eight babies were admitted in NICU for MSL and had good prognosis. The most common side effect of the drug was nausea (15%) followed by fever and vomiting. 69% patients did not have any adverse drug reaction. Conclusions: Thus, induction of labour with oral misoprostol reduces the LSCS rates, lesser induction delivery interval and has good fetal outcome. The drug is well tolerated by the patients orally and has very few side effects.